EXTH-31. BRAIN DISTRIBUTION, CLEARANCE AND TOXICITY EVALUATION OF SMALL-MOLECULE INHIBITORS FOLLOWING CONVECTION-ENHANCED DELIVERY TO THE BRAINSTEM. (12th November 2021) - Power, Erica; Oh, Juhee; Choi, Jonghoon; Elmquist, William; Daniels, David
Abstract: BACKGROUND: Diffuse midline gliomas (DMGs) harboring the H3K27M mutation are highly aggressive, fatal brainstem tumors that primarily occur in children. The blood-brain barrier (BBB) prevents numerous drugs from reaching CNS tumors, like DMG, at cytotoxic concentrations. Convection-enhanced delivery (CED) has emerged as a drug delivery technique that bypasses the BBB through a direct interstitial infusion under a pressure gradient. However, drug distribution and clearance from the brain following CED is poorly understood and has been cited as a potential reason for the lack of efficacy observed in prior clinical trials. OBJECTIVE: The objective of this study was to understand how two small molecule inhibitors (alisertib, ponatinib) that inhibit cell growth and proliferation in DMG cells in vitro distribute and clear from the brain following CED to the brainstem. METHODS: Sprague-dawley rats underwent a single 60mL CED infusion of drug to the brainstem (200mM alisertib, 10mM ponatinib) and were sacrificed 0.083, 1, 2, 4, 8 and 24 hours following the completion of the infusion. Brains were dissected and drug concentration was determined via HPLC analysis. RESULTS: No rats showed any clinical or neurological signs of toxicity post-infusion. Both drugs showed significant differences in drug concentration based on anatomical brain region where higher concentrations were observed in the pons and cerebellum compared to the cortex. Drug half-life in the brain was ~0.5 hours for alisertib and ~1 hour for ponatinib, but this was not significantly increased following co-administration of elacridar, a BBB efflux pump inhibitor. CONCLUSIONS: These results suggest that elimination of drugs from the brain in a complex, multifactorial mechanism that warrants further preclinical investigation prior to the initiation of a clinical trial.